Interpersonal violence in a deprived Scottish urban area with aggregations of physical health risks and psychiatric morbidity: an ecological study - Jeremy Coid; Yingzhe Zhang; Simone Ullrich; Jane Wood; Vishal Bhavsar; Paul Bebbington; Kamaldeep Bhui (BMC, 2021)
Abstract Background Glasgow, Scotland, has previously shown exceptional levels of violence among young men, shows aggregations of health conditions, with shortened life expectancy. Health conditions can be both causes and consequences of violence, of shared community-level socio-economic risk factors, and can result from large-scale social forces beyond the control of populations with high levels of violence. The aim of the study was to provide an in depth understanding of the Public Health problem of violence among young adult men in Glasgow East. Method Ecological investigation of violence and its associations with health conditions in areas of contrasting socioeconomic deprivation. National survey of 1916 British men aged 18-34 years, augmented by a sub-sample of 765 men in Glasgow East (GE). Participants completed questionnaires covering current physical and sexual health, psychiatric symptoms, substance misuse, lifestyle, and crime and violence. Results The 5-year prevalence of violence was similar in both surveys but fights involving weapons (AOR 3.32, 95% CI 2.29-4.79), gang fights (AOR 2.30, 95% CI 1.77-2.98), and instrumental violence supporting criminal lifestyles were more common in GE, where 1 in 9 men had been in prison. Violent men in both samples reported poorer physical and sexual health and all types of psychiatric morbidity except depression, with multiple high-risk behaviours for both future poor health and violence. Associations between drug and alcohol dependence and violence in GE could not be entirely explained by deprivation. Conclusion Violence in deprived urban areas is one among many high-risk behaviours and lifestyle factors leading to, as well as resulting from, aggregations of both psychiatric and physical health conditions. Poverty partly explained raised levels of violence in GE. Other factors such as drug and alcohol misuse and macho attitudes to violence, highly prevalent among men in this socially excluded community, also contributed. Multi-component preventive interventions may be needed in deprived areas and require future investigations into how multiple co-existing risk factors produce multimorbidity, including psychiatric disorders, substance misuse, poor physical health and violence.